Investigating teachers' pedagogic practices of argumentative essay: a qualitative case study of two Grade 11 classrooms in the Oshikoto Region, Namibia - Kanyama, Victoria Magano (Rhodes University, Faculty of Education, Department of Education, 2017)
Argumentative writing in Namibian schools has been a challenge over the years as Grade 11-12 English Second Language (ESL) learners perform poorly when compared to other writing that is stipulated in the curriculum. In most instances learners do not satisfy the structural and rhetorical features of this genre. English teachers are, therefore, expected to ensure that argumentative writing is adequately developed in order for the learners' writing to be up to the required standard. Studies carried out in Namibia by Nghikembua (2013) and Nyathi (2009) indicated that learners perform poorly in writing. The examiners' reports of 2011-2014 pointed to lack of teachers' guidance as one of the factors contributing to poor performance. It was for this reason that this study aimed to investigate teachers' pedagogic approaches when teaching argumentative essay both on Higher and Ordinary Level in Oshikoto region, Namibia. An interpretive qualitative case study was used in order to gain an in-depth understanding of the teachers' pedagogic approaches and how it affects their learners' argumentative essay writing. The theoretical framework was informed by the Genre theorist, Gibbons (2002), who focuses on the Curriculum Cycle and Hyland's (1990) model. Two Grade 11 English teachers were purposefully and conveniently sampled. One of the teachers is from a government school while the other from a private school. Data were collected from interviews, videoed writing lessons (3 per teacher), and learners' written essays. Data analysis revealed that both teachers have a sound understanding about argumentative writing, but their classroom practices did not sufficiently assist the learners to grasp the argumentative writing conventions. Their classroom practices were not adaptive enough when giving feedback to the learners, and they did not adhere to the four steps of Gibbons' (2002) Curriculum Cycle. Also, the process to writing (brainstorming, drafting, and revising) was also not incorporated into their teaching. These meant that the Namibian curriculum specifications are not met which deprives the learners of the needed practice scaffolding and explicit teaching into competent independent writers. A recommendation of this study is that there is a need for the teachers to be exposed to a mixed process/genre approach as advocated by the Namibian curriculum.
Keywords: Persuasion (Rhetoric) -- Study and teaching (Secondary) -- Namibia; English language -- Rhetoric -- Study and teaching (Secondary) -- Namibia; English language -- Writing -- Study and teaching (Secondary) -- Namibia